Subtitling strategies of imperative sentence from English into Indonesian in the Divergent Series: Insurgent movie - Farra Aziizah Ade Fitri; Romel Noverino (Lililacs Journal: English Literature, Language, and Cultural Studies Journal, 2023)
The topic of this research is subtitling strategies of imperative sentence in The Divergent Series: Insurgent movie. The aims of this research is to find out the kind of subtitling strategies in the movie. This research used a descriptive method. The source data for this research are English subtitle and Indonesian subtitle from The Divergent Series: Insurgent movie. The data in this research is the dialogue in the movie. The researcher used the theory from Gottlieb (1992). The result of this research there are 8 kind of subtitling strategies, there are 73 data classified as Paraphrase, 32 data classified as Transfer, 13 data classified as Expansion, 21 data classified as Imitation, 4 data classified as Condensation, 5 data classified as Decimation, 12 data classified as Deletion, and 5 data classified as Resignation. The most subtitling strategy that used in this research is Paraphrase strategy because there are 73 data classified as Paraphrase strategy.